2007
DOI: 10.1128/jb.00437-07
|View full text |Cite
|
Sign up to set email alerts
|

FepA- and TonB-Dependent Bacteriophage H8: Receptor Binding and Genomic Sequence

Abstract: H8 is derived from a collection of Salmonella enterica serotype Enteritidis bacteriophage. Its morphology and genomic structure closely resemble those of bacteriophage T5 in the family Siphoviridae. H8 infected S. enterica serotypes Enteritidis and Typhimurium and Escherichia coli by initial adsorption to the outer membrane protein FepA. Ferric enterobactin inhibited H8 binding to E. coli FepA (50% inhibition concentration, 98 nM), and other ferric catecholate receptors (Fiu, Cir, and IroN) did not participate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
73
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(81 citation statements)
references
References 102 publications
5
73
0
2
Order By: Relevance
“…In phage T5, the antireceptor, the monomeric gp5, associates tightly (subnanomolar) with a siderophore transport porin, FhuA (22). This mechanism is observed with two other phages, BF23, whose antireceptor binds to BtuB (23), a B12 vitamin transporter, and H8, which attaches to FepA, another iron transporter (24). The lactococcal phage c2 has been shown as well , and 53 is assembled in a large hexagonal structure.…”
Section: Discussionmentioning
confidence: 90%
“…In phage T5, the antireceptor, the monomeric gp5, associates tightly (subnanomolar) with a siderophore transport porin, FhuA (22). This mechanism is observed with two other phages, BF23, whose antireceptor binds to BtuB (23), a B12 vitamin transporter, and H8, which attaches to FepA, another iron transporter (24). The lactococcal phage c2 has been shown as well , and 53 is assembled in a large hexagonal structure.…”
Section: Discussionmentioning
confidence: 90%
“…[52][53][54] We found that CEV2, like T5, does not require an energized membrane or the presence of TonB. [55][56][57] Our finding that CEV2 is a close relative of T5 is advantageous; T5-like phages are exclusively lytic and none have been found to encode pathogenicity islands, virulence/antibiotic resistance genes or integrases. 49,58 To our knowledge, CEV2 is the first T5-like phage to be isolated that infects E. coli O157:H7.…”
Section: Discussionmentioning
confidence: 99%
“…In more divergent bacterial species, maltodextrins, sucrose, and Ni 2ϩ reflect the tip of the iceberg of nutrients that require TonB system energy transduction for transport across the OM (for reviews, see references 2, 21, 22, 31, 36, and 41). Bacteriophages and many colicins have evolved to make use of the TonB system to enter E. coli (9,39,42). Sensitivity to these reagents and ability to transport iron siderophores are the initial phenotypic assays usually applied to TonB system mutants.…”
mentioning
confidence: 99%